Soil and groundwater investigation in Kuala Selangor coastal plain using geoelectrical and geochemical surveys - Umar Hamzah; Abdul Rahim Samsudin; Edna Pills Malim (Universiti Kebangsaan Malaysia, 2006)
An integrated geoelectrical and geochemical techniques were used to investigate and delineate different types of groundwater in Kuala Selangor-Batang Berjuntai alluvial aquifer. Previous hydrogeological borehole investigations showed that this aquifer contained several types of groundwater in relation to its salinity. The high salinity of the groundwater in some areas was believed to be due to either saltwater intrusion from the nearby sea or river infiltration during tide season. Both vertical electrical sounding (VES) and 2-D electrical resistivity imaging methods were employed to study and map the subsurface variation of resistivity in the area. For each measurement, a total spread length of 200 m was obtained with vertical depth penetration of about 60 to 100 m. Chemical analysis data of the groundwater samples taken from both shallow and deep boreholes were used in the interpretation of the groundwater interfaces. A total of 45 VES stations were succesfully established along three parallel roads with direction almost perpendicular to the coastal line. The distance between stations vary from 1 - 2 km with a maximum length of about 60 km surveyed line. Results of the vertical electrical soundings and resistivity imaging as well as the chemistry of the groundwater samples showed that groundwater in the study area can be grouped into three types i.e. fresh water (resistivity >100 Ωm.), brackish water (5-100 Ωm.) and salt water (resisitvity <5 Ωm.). The subsurface resistivity sections derived from the VES study suggest that the boundary between fresh and salt water was located between 4 to 8 km from the present coastal line. This result appears to agree well with the groundwater interfaces obtained from the chloride concentration map. Values greater than 300 ppm was considered to be representing zone of brackish water whilst values greater than 800 ppm represents saline water zones.